Dysregulated thyroid hormones correlate with anxiety and depression risk in patients with autoimmune disease. Issue 1 (18th November 2020) - Wu, Xiaorong; Zhang, Kaikai; Xing, Yulong; Zhou, Wei; Shao, Yanqiu; Li, Guizheng; Rui, Qing
Abstract: Background: Autoimmune disease (AID) patients always present with increased risk of psychiatric disorders, and thyroid function or thyroid hormone may play a critical role in the development of anxiety and depression. Thus, this study aimed to assess the free triiodothyronine (FT3), free tetraiodothyronine (FT4), thyroid‐stimulating hormone (TSH) levels, and their correlations with anxiety/depression in patients with AID. Methods: Ninety‐eight AID patients and 100 health controls (HCs) were recruited. Serum samples were obtained from all the participants to detect FT3, FT4, and TSH levels. Anxiety and depression were determined using the HADS assessment. Results: HADS‐Anxiety score, anxiety subject percentage, HADS‐Depression score, and depression subject proportion were elevated in AID patients compared with HCs. FT3 and FT4 were downregulated while TSH was upregulated in AID patients compared with HCs. In AID patients, FT3 and FT4 negatively correlated with HADS‐Anxiety score, and they were downregulated in patients with anxiety compared to patients without anxiety. Meanwhile, FT3 and FT4 were negatively associated while TSH level positively associated with HADS‐Depression score. Besides, FT3 and FT4 reduced, but TSH level was of no difference in patients with depression compared to patients without depression. Additionally, increased FT4 independently correlated with both reduced anxiety risk and depression risk. Conclusions: FT3, FT4, and TSH are dysregulated, and FT4 has the potential to serve as an independent biomarker related to anxiety as well as depression in AID patients. These findings may provide some information on the values of thyroid hormones in facilitating the management of AID patients with anxiety/depression. Abstract : Background: This study aimed to assess the free triiodothyronine (FT3), free tetraiodothyronine (FT4), thyroid‐stimulating hormone (TSH) levels, and their correlations with anxiety/depression in patients with autoimmune disease (AID). Methods: Ninety‐eight AID patients and 100 health controls (HCs) were recruited. Then serum samples were obtained from all the participants to detect FT3, FT4, and TSH levels. Anxiety and depression were determined using the Hospital Anxiety and Depression Scale (HADS) assessment. Results: HADS‐Anxiety (HADS‐A) score ( P < .001), anxiety subject percentage ( P = .002), HADS‐Depression (HADS‐D) score ( P < .001), and depression subject proportion ( P < .001) were notably elevated in AID patients compared to HCs. Most interestingly, FT3 ( P < .001) and FT4 ( P < .001) levels were downregulated while TSH level ( P < .001) was upregulated in AID patients compared to HCs. In AID patients, FT3 ( P = .004) and FT4 ( P = .001) levels were negatively correlated with HADS‐A score, and they were downregulated in patients with anxiety compared to patients without anxiety ( P = .025 and P < .001, respectively). Meanwhile, FT3 ( P = .010) and FT4 ( P < .001) levels were negatively associated while TSH level ( P = .041) was positively associated with HADS‐D score. Besides, FT3 ( P = .003) and FT4 ( P < .001) levels were reduced, but TSH level was of no difference in patients with depression compared to patients without depression. Multivariate logistic regression analysis revealed that increased FT4 level was independently correlated with both reduced anxiety risk ( P = .001) and depression risk ( P < .001). Conclusions: FT3, FT4, and TSH are dysregulated, and FT4 has the potential to serve as an independent biomarker related to anxiety as well as depression in AID patients.